Experiences of Early Childhood Caregivers in Times of Covid-19 Pandemic Confinement - Henríquez, Lizeth Paola Hernández; Henríquez, Cindy Paola Hernández; Chamorro, Mónica Isabel Herazo; Hernández, Patricia Mendivil; Sánchez, Eduardo González (Journal of Ecohumanism, 2025)
The objective of the study was to analyze the creative experiences of caregivers of children in early childhood in a children's home in times of confinement due to the COVID-19 pandemic, from a qualitative approach with a phenomenological design. The in-depth study was carried out with six families, three nuclear and three extended, selected under the theoretical or conceptual sample; a semi-structured interview was applied as an instrument for the collection of information. From the experience of the participants, the results allowed us to establish domestic work, protection, adaptability and emotional support as the main activities assumed by the caregivers in the midst of confinement. Likewise, diversity in caregiving was visualized in the insertion of multiple caregiving functions that generated caregiver overload. Finally, the permanence of caregiving, the strengthening of emotional bonds and the woman as the main protagonist were reflected as particular elements in the caregiving experiences of the participants.